CONSTRUCTIVE AND FUNCTIONAL CONSIDERATIONS FOR USING THERMALLY INSULATED ENCLOSURE IN 3D RESIN PRINTING PROCESS (Nonconventional Technologies Review, 2020)
A comparative study is carried out in the paper, which aims to determine the need to position a 3D print inside a thermally insulated enclosure. Print the same piece under layout conditions inside an office space and then insert it inside a thermally insulated enclosure made by the author. From the point of view of temperature loss, better management of the thermal process can be achieved from the point of view of the printing process. Also at the level of the printed plane made we can see a reduction in internal tensions in the item due in particular to the temperature variations in the printing process for the printed item in the two 3D printing variants.
Keywords: enclosure for printerLP 3D Printing; Arduino control system